The Appeal for People's Power: Legal Perspectives In The 2019 Presidential And Vice-Presidential General Elections - Riyady, Slamet (Yayasan Sinergi Kawula Muda, 2023)
On April 17, 2019, Indonesia conducted a simultaneous general election involving five ballots for various political offices. The objective was to reduce election costs and improve efficiency. Despite a well-established electoral system, certain political elites contested the results using calls for 'people power.' This research aims to examine the legal implications of such calls and their compatibility with the law. Using a normative approach and legal behavior case studies, this study utilizes primary data from laws and secondary sources, such as books on democracy and freedom of expression. The theoretical contribution lies in clarifying that freedom of expression should not be considered seditious, as sedition entails efforts to overthrow the government. However, if demonstrators violate regulations, particularly Article 6 of the Freedom of Expression Law, it may be considered sedition. It is recommended to handle the results of the presidential and vice-presidential elections maturely by entrusting them to the competent authority, the Constitutional Court.